Dangerous Play - Deborah Hardt (Humanimalia)
Since 2020, orcas off the coast of the Iberian Peninsula have been ramming boats with their bodies, causing damage and, in some cases, sinking vessels. To this day, more than 500 incidents have taken place. Scientists are reluctant to call the events intentional acts of aggression and report that what the orcas are doing can be categorized as play.